The Importance of the Humanities: Reflections from Leading Policymakers - Silka, Linda (Maine Policy Review, 2015)
Maine is fortunate in being served by state policy leaders who care deeply about the humanities and who have devoted considerable thought to the role of the humanities in Maine’s past, present, and future. In this article, Linda Silka interviews four of these leading policymakers about the humanities and policy: Tom Desjardin, Peter Mills, Margaret (Peggy) Rotundo, and Earle G. Shettleworth Jr.
Keywords: humanities; policymakers; Maine